Predicting the Role of Public-Private Partnerships in Future Public Health Crises: A Qualitative Scenario Analysis - Eslami, Fereydon; Hooshmandi, Roodabeh (Journal of Foresight and Health Governance, 2024)
This study aims to explore the strategic role, challenges, and future potential of public-private partnerships (PPPs) in managing public health crises. This study employed a qualitative research design using semi-structured interviews with 22 participants, including policymakers, healthcare administrators, private sector executives, and emergency management specialists. Participants were recruited through online announcements and professional platforms. Theoretical saturation was achieved, ensuring comprehensive data collection. Interviews were transcribed and analyzed using NVivo software, applying thematic analysis to identify key themes related to the effectiveness, barriers, and future strategies of PPPs in public health crisis management. The results highlighted the strategic role of PPPs in expanding healthcare infrastructure, optimizing resource allocation, and integrating technological solutions such as AI-driven health monitoring and shared data systems. However, significant barriers, including regulatory constraints, financial misalignment, and trust deficits, were identified as major challenges to effective implementation. Participants emphasized the need for adaptive policy frameworks, sustainable financing models, and cross-sector collaboration to enhance the resilience and efficiency of PPPs. Additionally, capacity-building initiatives and improved crisis communication strategies were identified as crucial for strengthening public-private collaborations in health emergencies. Public-private partnerships have the potential to significantly improve public health crisis management, but their effectiveness is contingent on overcoming regulatory, financial, and trust-related barriers. Future efforts should focus on enhancing policy flexibility, fostering sustainable financial models, and leveraging technology to strengthen crisis response mechanisms. Strategic interventions that align organizational priorities and promote transparency will be critical for optimizing the role of PPPs in future public health emergencies.